2002
DOI: 10.1034/j.1600-0412.2002.810306.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcome of failure to progress during the first stage of labor: a population‐based study*

Abstract: Major risk factors for failure of labor to progress during the first stage were PROM, nulliparity, induction of labor and older maternal age. Indications for labor induction should be carefully evaluated in order to decrease the rate of operative deliveries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 36 publications
(39 reference statements)
7
52
1
Order By: Relevance
“…5,9 The anticipated continuing temporal changes in these maternal characteristics and obstetric practice patterns predict increasing rates of caesarean delivery in labour. While previous studies have evaluated the risks of adverse maternal, fetal and neonatal outcomes associated with caesarean delivery in labour by comparing caesarean with other methods of delivery 5 and by duration of labour, 6,9 a review of the literature found no reports assessing the risks of maternal or perinatal morbidity following caesarean delivery by stage of labour (full cervical dilatation compared with less than full dilatation).…”
Section: Discussionmentioning
confidence: 99%
“…5,9 The anticipated continuing temporal changes in these maternal characteristics and obstetric practice patterns predict increasing rates of caesarean delivery in labour. While previous studies have evaluated the risks of adverse maternal, fetal and neonatal outcomes associated with caesarean delivery in labour by comparing caesarean with other methods of delivery 5 and by duration of labour, 6,9 a review of the literature found no reports assessing the risks of maternal or perinatal morbidity following caesarean delivery by stage of labour (full cervical dilatation compared with less than full dilatation).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study of >90,000 deliveries 16 , found that women who carried a male fetus were at a 20% increased risk to be diagnosed with an arrest disorder and undergo cesarean delivery in the first stage of labor compared with women who carried a female fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Association between Fetal Gender... cesarean delivery [3][4][5] . This finding has been interpreted as a surrogate for fetal size because male fetuses tend to be larger on average compared with female fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative for labor augmentation in grandmultiparous with hypotonic uterine contractions (i.e., breast stimulation) is of unproved eYcacy and safety. Limiting the use of oxytocin in GMPs might lead to higher rates of cesarean deliveries, due to labor dystocia [6,12]. The present editorial was conducted in order to determine policies toward the use of oxytocin for labor augmentation among grandmultiparous patients.…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin is commonly used for labor augmentation, especially in cases where labor fails to progress according to Friedman's curve [6,7,12]. However, the use of oxytocin in grandmultiparous parturients (GMPs) (above 5 deliveries) as well as in patients with a scarred uterus is believed to expose them to a higher rate of peripartum complications including uterine rupture [13,15].…”
Section: Introductionmentioning
confidence: 99%